2021
DOI: 10.1097/md.0000000000026394
|View full text |Cite
|
Sign up to set email alerts
|

Teaching ultrasound-guided peripheral venous catheter placement through immersive virtual reality

Abstract: Introduction: Immersive virtual reality (IVR)-based training is gaining ground as an educational tool in healthcare. When combined with well-established educational methods, IVR can potentially increase competency and autonomy in ultrasound (US)-guided peripheral venous cannulation. The aim of this study was to examine the impact of adding IVR training to a course in US-guided peripheral venous cannulation. Methods: Medical students (n = 19) from the Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“… 6 , 17 , 19 21 , 23 , 37 Three studies incorporated pre-recorded videos for training purposes. 22 , 37 , 38 Two studies used experiential learning to help medical professionals understand the difficulties that patients faced, such as language barriers, cultural barriers, financial limits, or the impact of the disease. 24 , 37 Two studies provided additional web-based VR materials or resources to participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 , 17 , 19 21 , 23 , 37 Three studies incorporated pre-recorded videos for training purposes. 22 , 37 , 38 Two studies used experiential learning to help medical professionals understand the difficulties that patients faced, such as language barriers, cultural barriers, financial limits, or the impact of the disease. 24 , 37 Two studies provided additional web-based VR materials or resources to participants.…”
Section: Resultsmentioning
confidence: 99%
“…One study focused on learning efficacy. 22 The VR-based training simulation centered on tip tracking abilities in order to improve medical students’ learning efficacy in placing peripheral venous cannulas. The VR group had a considerably higher proportion of successful cannula emplacements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastering the skill and procedures of puncture or catheterization is essential across many medical specialties. However, as an invasive operation that may cause patients discomfort and have the risk of complications, puncture or catheterization has been considered as a challenge for medical training ( 63 , 99 ). In the recent 2 years, three published articles reported the application of VR in VS training among medical undergraduates for lumbar puncture ( 25 ), ultrasound-guided peripheral venous catheter placement ( 63 ), and endotracheal intubation ( 99 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, as an invasive operation that may cause patients discomfort and have the risk of complications, puncture or catheterization has been considered as a challenge for medical training ( 63 , 99 ). In the recent 2 years, three published articles reported the application of VR in VS training among medical undergraduates for lumbar puncture ( 25 ), ultrasound-guided peripheral venous catheter placement ( 63 ), and endotracheal intubation ( 99 ), respectively. The results collectively suggested that, as a teaching method well-received by students, VS training can engage learners, develop their practical competencies and proficiency in performing procedures under safe and controlled environments, facilitate spatial recognition and anatomic visualization, thus enhance medical education and skills training ( 25 , 63 , 99 ).…”
Section: Resultsmentioning
confidence: 99%